Tomato breeding for disease resistance - de Almeida, Gabriella Queiroz (2020)
In the genetic breeding of tomatoes, not only productivity, but also factors related to fruit quality and pest and disease management are taken into account. In this context, diseases stand out, since they are the main bottlenecks for successful cultivation. Currently, the search for more sustainable crops has demanded from producers’ alternatives to disease control to reduce the use of pesticides. Among the diseases that most reduce tomato production in Brazil, whether for table or industry, we can mention late blight, black spot, fusarium wilt, viruses, bacterial and nematode diseases. Genetic resistance, obtained by genetic breeding programs, is one of the best tools to deal with diseases to depend less on pesticides. Thus, this review aims to provide an overview of tomato breeding programs in terms of resistance to the main diseases that affect this crop.